A modeling study of estuarine–shelf circulation using a composite tidal and subtidal open boundary condition. (March 2020) - Liu, Zhiqiang; Gan, Jianping
Abstract: We investigated the performance of a tidally and subtidally forced open boundary condition (TST-OBC) on the estuarine–shelf circulation in a limited-area, down-scaling numerical modeling system for the northern South China Sea. We forced the modeling system with amplified tidal forces and subtidal forcing of spatiotemporally variable wind and river discharge. TST-OBC numerically and physically accommodates the circulation driven by the regional tides, subtidal forces, external forcing from its upscale solution, and internally generated disturbances. The advantages of TST-OBC are the separation of fast tidal and slow subtidal modes, active and dual-wave transmitting schemes, consistent treatment of barotropic and baroclinic circulation, and thermodynamic variables, which enable the model to capture observed circulation characteristics. The results differ from the results obtained using the Flather-type OBC, which over-restores internal to external solutions with a notable accumulation of spurious disturbances along the open boundaries. Disturbances with both tidal and subtidal signals that arrive at the open boundaries are well-treated by adopting TST-OBC, although it is currently feasible for the one-way downscaling applications. Highlights: A tidal-subtidal open boundary condition is used for simulating ocean circulations. The TST-OBC is capable to resolve tidal and subtidal disturbances simultaneously. A consistent usage of active scheme for all variables improves numerical downscaling.